Derywacja stylistyczna w nauczaniu obcokrajowców różnych odmian współczesnej polszczyzny - Miodunka, Władysław (Stylistyka, 1996)
Referring to the notion of stylistic derivation introduced to the Polish linguistics by Jerzy Bartmiński, the author regards a colloquial (conversational) style as the basic one. He considers, on the basis of analysis, model texts from various textbooks of Polish to belong to a neutral and elaborated variants of the colloquial style, while the texts from • medical, humanistic and technical textbooks of Polish, he presents as the derivates of the colloquial style introducing at the same time the notion of derivation of the first and the second degree. He speaks about the derivation of the first degree when a new stylistic variant includes lexical, grammatical and syntagmatic means known also in the colloquial style, yet selected with care to create a new homogenous text. The derivation of the second degree takes place when a new stylistic variant includes lexical, grammatical and syntagmatic means not known in the conversational style.